CYBER COUNSELING SEBAGAI SALAH SATU MODEL PERKEMBANGAN KONSELING BAGI GENERASI MILENIAL - DYAH LUTHFIA KIRANA (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
The development of technology and communication provides convenience and extends the space for the movement of society today. Most of the activities of society are no longer limited by space and time, anytime and anywhere. The use of social media is high in proportion to the development of millennial generation who are familiar with technology. This generation has the characteristics of open communication, fanatical social media users, their lives are greatly affected by technological developments. Professional counselors must create a creative and innovative ways, strategies or methods to support guidance and counseling services for the millennial generation. Cyber Counseling is a services form of innovation and breakthrough in the world of counseling for millennials. Some Cyber Counseling methods that have been used by counselors include: E-mail-based Cyber-counseling, Android-based Cyber-Counseling Chat, Text-Based Cyber ??Counseling Using Riliv Android Applications, and Facebook-based Cyber ??Counseling.